2006
DOI: 10.4103/0019-5359.19912
|View full text |Cite
|
Sign up to set email alerts
|

Demyelinating disease simulating brain tumours: A histopathologic assessment of seven cases

Abstract: BACKGROUND: Demyelinating diseases can present as space occupying lesions with in the brain. It is clinically and radiologically difficult to differentiate them from primary neoplasms. Histopathologically they mimic astrocytic neoplasms closely and identifying these lesions correctly has a profound impact in treatment and prognosis of these patients. AIMS AND OBJECTIVES: The objective was to determine the histopathologic features of such acute focal demyelinating disease that clinically presented as brain tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…One study suggested that these lesions are not associated with necrosis [9], but a separate study demonstrated central necrosis within these lesions [4]. In our case, the lesion showed abundant necrosis.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…One study suggested that these lesions are not associated with necrosis [9], but a separate study demonstrated central necrosis within these lesions [4]. In our case, the lesion showed abundant necrosis.…”
Section: Discussioncontrasting
confidence: 42%
“…In a retrospective review of 40 patients with biopsy or autopsy-proven demyelinating lesions, only three patients had minimal oedema and mass effect, while one patient had moderate oedema and severe mass effect on radiological imaging [3]. Three case reports describing cerebral demyelinating lesions also demonstrated conflicitng evidence in relation to the presence of mass effect surrounding these lesions on radiological imaging [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory demyelinating pseudotumor (IDMP) is a puzzle to clinicians, radiologists and pathologists due to many overlapping features (1,(3)(4)(5)7). Pathogenesis of IDMPs is not clear and it is different from multiple sclerosis and acute disseminated encephalomyelitis (9).…”
Section: Discussionmentioning
confidence: 99%
“…It is very difficult to differentiate these lesions from brain tumors as there is a considerable clinico-radiological overlap and it becomes nearly impossible to differentiate on routine cross sectional imaging when they present with hemorrhage or show complete rim enhancement (1,3,4,8). Subsequent relapse of symptoms and the presence of multiple abnormal signal intensity plaques, should raise suspicion of demyelinating pseudotumor (5).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation